Spatial effects of highways on employment in Missouri - 김용렬 (한국농촌경제연구원, 2007)
The purpose of this paper is to determine if there is a relationship between highway development and the spatial pattern of employment growth in Missouri. In order to determine if there is a spatial pattern to the employment growth in the county, a spatial lag model was estimated and contrasted with a simpler model that did not consider spatial relationships. My intention is to figure out how highways in a county and neighboring counties affect the employment of that county. Interstate highways in Missouri are shown not to have positive effects on employment growth. The “mileage of four-lane roads in a county” variable has significant and negative effects on employment growth. The “number of miles of two-lane roads within a county” variable has an insignificant and negative effect. In addition, “two lane road mileage in surrounding counties” has insignificant and positive effects. The spatial autoregressive coefficient (ρ) is significantly positive, implying that there is a positive spatial interaction between the counties. Results suggest that road networks that are too dense can have negative impacts on employment growth in a county, and that highway overinvestment may lead to diminishing employment returns in Missouri.
Keywords: employment; highway; spatial lag model; Missouri; employment; highway; spatial lag model; Missouri